Wind farm control part II: Model requirements to design and test wind farm flow control - Adam Stock; Scott Dallas; Valentin Chabaud; Konstanze Kölle; Laurence Morgan; John Olav Tande; Olimpo Anaya‐Lara (IET Renewable Power Generation)
Abstract Wind farm flow control (WFFC) is an emerging technology involving coordinated operation of wind turbines within a wind farm to achieve collective goals. To design and evaluate controllers, wind farm flow models are used that capture the key aerodynamics of the system whilst remaining computationally efficient for iterative controller design. This review article reveals considerable heterogeneity in the potential wind farm flow models to study WFFC. Lack of consensus is problematic as differences in results from separate studies are attributable to both controller and model effects, making it hard to draw comparative conclusions. Hence, an expert elicitation is completed surveying WFFC practitioners. Two key contributions are presented. First, a guide to available software for WFFC, which, combined with results from an expert elicitation on flow model requirements, facilitates selection of suitable software for investigating WFFC problems. Secondly, critical future research areas are identified. Research into high fidelity wind direction models (particularly transient effects) and wake meandering models for fatigue load investigations are identified as critical to the field. A lack of consensus regarding the importance of atmospheric boundary layer effects, wake induced turbulence, and lateral wind correlation identifies the requirement of sensitivity studies in these areas.